2019
DOI: 10.1111/jne.12666
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological properties of identified oxytocin and vasopressin neurones

Abstract: To understand the contribution of intrinsic membrane properties to the different in vivo firing patterns of oxytocin (OT) and vasopressin (VP) neurones, in vitro studies are needed, where stable intracellular recordings can be made. Combining immunochemistry for OT and VP and intracellular dye injections allows characterisation of identified OT and VP neurones, and several differences between the two cell types have emerged. These include a greater transient K+ current that delays spiking to stimulus onset, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 189 publications
(324 reference statements)
0
16
0
Order By: Relevance
“…These neurones have some features that distinguish them clearly from most other hypothalamic neurones, and some features that are more commonly observed in vasopressin cells than in oxytocin cells, and vice versa, although there is considerable variation within each of these populations. 81 A few cells appear to have an ambiguous phenotype; for example, a few cells not only generate both suckling-induced milk-ejection bursts, classically identifying them as oxytocin cells, but also show phasic firing patterns that are mainly associated with vasopressin cells. Most magnocellular neurones express mRNAs for both oxytocin and vasopressin; usually, these are present at very different levels, although a small proportion (approximately 3%) express both at equivalent levels.…”
Section: Wider Inferencesmentioning
confidence: 99%
“…These neurones have some features that distinguish them clearly from most other hypothalamic neurones, and some features that are more commonly observed in vasopressin cells than in oxytocin cells, and vice versa, although there is considerable variation within each of these populations. 81 A few cells appear to have an ambiguous phenotype; for example, a few cells not only generate both suckling-induced milk-ejection bursts, classically identifying them as oxytocin cells, but also show phasic firing patterns that are mainly associated with vasopressin cells. Most magnocellular neurones express mRNAs for both oxytocin and vasopressin; usually, these are present at very different levels, although a small proportion (approximately 3%) express both at equivalent levels.…”
Section: Wider Inferencesmentioning
confidence: 99%
“…This is because PGE 2 can evoke more than 70% of oxytocin neurons to discharge burst firing in brain slices, while oxytocin can evoke the burst in less than 30% of oxytocin neurons ( Wang et al., 2016 ). The burst firing in oxytocin neurons has been linked to a rebound firing feature of oxytocin neurons ( Armstrong et al., 2019 ). Among several known ion channels on oxytocin neurons, hyperpolarization-activated cyclic nucleotide-gated channels (HCNs) have the feature of rebound excitation and burst-evoking ability ( Qiu et al., 2005 ; Ying et al., 2011 ).…”
mentioning
confidence: 99%
“…Electrophysiological studies on VGCC currents showed that the soma of rat supraoptic MNCs functionally express T-, N-, L-, P/Q-and R-type Ca 2+ channels [25][26][27][28][29]. However, increasing evidence has shown that there are some differences in important properties including ion channel activities and firing patterns between AVP and OXT neurons [30]. Thus, further studies have been warranted to be performed on VGCC activities in AVP neurons by distinguishing from those in OXT neurons, and vice versa.…”
Section: Discussionmentioning
confidence: 99%